Les relations entre l’âge et le travail comme problème temporel - Corinne Gaudart (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article examines – using an ergonomic approach - the relation between age and work from the angle of time and the growing problem of numerous social, management, collective, and individual temporalities. These different temporalities organize time and structure age-work relations into configurations that lead to temporal conflicts. Work activity can be seen as a temporal crossroad that combines these temporalities synchronically and diachronically. It becomes a space where temporalities are organized and where the ability to produce time comes into play. The age-work relation is examined from three angles: repetitive work as “tight” time, the organization of time through collective work and specific occupations, and occupational knowledge transmission between older and new workers as an experience that transcends the temporalities of the workers’ lifecycles.